Evaluation of prognostic factors effecting mortality in gastroschisis patients [Gastrosizis olgularinda mortaliteyi etkileyen unsurlar] - (:unkn) unknown (My University, 1997)
In this clinical study, we evaluated retrospectively, the factors effecting mortality in gastroschisis patients operated in our clinic during the past five years. In 17 cases between 1992-1997, gestational age, birth weight, body temperature on admission, mode and complications of treatment, need for ventilatory support, duration of total parenteral nutrition (TPN), onset of enteral feeding and causes of death were analyzed. Primary closure was possible in eleven patients (64 %), where as in the remaining six mesh sheeting was needed and fascia closure was done after removal of the mesh in about 8.7 days. The overall mortality rate was 29 %. The difference between prematurity incidence and birth weight among deaths and survivors were significant (p<0.05) and all of the deaths were premature or small or gestational age babies. Three deaths among the total of five cases were due to serious metabolic acidosis. Differences in age on admission, body temperature and technique of abdominal wall closure were found to be insignificant. The results of our study indicates that prematurity, low birth weight and transport conditions are the major causes of mortality in our country.
Keywords: Abdominal wall defects; Gastroschisis